Online Information Delivery Service System Design Using Web-Based Forward Chaining Method in Pharmaceutical Companies - Eko Tri Asmoro; Ire Puspa Wardhani; Munich Heindari Ekasari (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
This online complaint or information submission application is a web-based application which is useful to assist employees obtain information online. Currently, the complaint and information submission are still using the old method by asking the question through the relevant employees manually. This way is inefficient in terms of time due to some employees are not always available in place. Therefore, with the development of technology, it encourages the researcher to design web-based application system which is useful for assisting employees to submit complaint and information. This design process using a Navigation Structure, Unified Modeling Language and Forward Chaining method as a data processor. Out of the two technology that have been tested (laptop and smartphone), this application works well on laptop, while on smartphone, the button layout does not appear, as well the display it does not respond horizontally or vertically. This application will be assist the pharmaceutical company employees to submit information and complaints anytime and anywhere easier.